Role of body mass index on physical fitness index in two - Haroonrashid M.Hattiwale (Al Ameen Medical College, 2008)
The body mass index (BMI) is an index of weight adjusted for hieght. It is one of the useful tools for diagnosing obesity or malnutrition; however, such diagnosis should take into account a person's age, gender, fitness, and ethnicity. The objective of this study was to evaluate the BMI and physical fitness index (PFI) of healthy subjects consists of early part and late part of youth of north interior Karnataka, India and also to find out the influence of BMI on PFI in same subjects as such study in this area is least done by competent researchers. Twenty five young, healthy adults belonging to age group of 17-21 years were selected as Group I and fifteen young healthy adults belonging to age group of 29-40 were selected as Group II subjects in this study. The present study reveals that physical anthropometric parameters were found to be within the expected range of normal in both Group I and Group II subjects of north interior Karnataka which reflects the adequate nutrition, socioeconomic status and normal life style of these individuals. In this study, no correlation was found between BMI and PFI score and a positive correlation was observed between BMI and waist hip ratio in both the age groups